Learning design research: Advancing pedagogies in the digital age - Dobozy, Eva (Taylor and Francis, 2013)
Learning design research (LDR) is establishing itself as a separate and specialised field of educational research. Worldwide, technology-mediated learning experiences in higher and further education are on the increase. LDR investigates their success in providing effective outcomes-based and personalised learning experiences. This paper reports on a meta-ethnographic review study of a subsection of current LDR to document current conceptualisations, preferred methodologies and possible themes and struggles. The findings suggest that LDR often uses an ad hock approach to Learning Design conceptualisation. It is concluded that the current ontological and epistemological disparity presents a great hindrance to the advancement of LDR.